The Drosophila Zinc Finger Transcription Factor Ouija Board Controls Ecdysteroid Biosynthesis through Specific Regulation of spookier. - Tatsuya Komura-Kawa; Keiko Hirota; Yuko Shimada-Niwa; Rieko Yamauchi; MaryJane Shimell; Tetsuro Shinoda; Akiyoshi Fukamizu; Michael B O'Connor; Ryusuke Niwa (PLoS Genetics)
Steroid hormones are crucial for many biological events in multicellular organisms. In insects, the principal steroid hormones are ecdysteroids, which play essential roles in regulating molting and metamorphosis. During larval and pupal development, ecdysteroids are synthesized in the prothoracic gland (PG) from dietary cholesterol via a series of hydroxylation and oxidation steps. The expression of all but one of the known ecdysteroid biosynthetic enzymes is restricted to the PG, but the transcriptional regulatory networks responsible for generating such exquisite tissue-specific regulation is only beginning to be elucidated. Here, we report identification and characterization of the C2H2-type zinc finger transcription factor Ouija board (Ouib) necessary for ecdysteroid production in the PG in the fruit fly Drosophila melanogaster. Expression of ouib is predominantly limited to the PG, and genetic null mutants of ouib result in larval developmental arrest that can be rescued by administrating an active ecdysteroid. Interestingly, ouib mutant animals exhibit a strong reduction in the expression of one ecdysteroid biosynthetic enzyme, spookier. Using a cell culture-based luciferase reporter assay, Ouib protein stimulates transcription of spok by binding to a specific ~15 bp response element in the spok PG enhancer element. Most remarkable, the developmental arrest phenotype of ouib mutants is rescued by over-expression of a functionally-equivalent paralog of spookier. These observations imply that the main biological function of Ouib is to specifically regulate spookier transcription during Drosophila development.